A new natural hybrid of Rosa (Rosaceae) from Turkey - Korkmaz, Mustafa; Kandemir, Ali; Yıldırım Doğan, Nalan (Phytotaxa, 2016)
In this study, Rosa × ozcelikii Korkmaz & Kandemir is described as a new natural hybrid between Rosa villosa subsp. mollis and R. hemisphaerica from material collected in Erzincan province (Turkey). It was compared with closely related species using morphological data. In addition, genetic relationships of the new hybrid with the putative parental taxa were determined by Random Amplified Polymorphic DNA (RAPD) and Inter Simple Sequence Repeat (ISSR) markers. Properties of soils in which the new hybrid grows in the wild are also presented.